Longer Brace Duration Is Associated with Lower Stress Levels and Better Quality of Life in Adolescents with Idiopathic Scoliosis - Fabrizio Di Maria; Gianluca Testa; Michela Carnazza; Martina Testaì; Vito Pavone (MDPI AG, 2023)
Physical and psychological health concerns have been raised due to either spine deformity or orthotic treatment in adolescents with idiopathic scoliosis. To determine whether orthotic bracing duration affects psychological stress and health-related quality of life, a sample of 46 patients (8M, 38F, aged 11-17 years, regularly treated with bracing) with moderate or moderate to severe idiopathic scoliosis were separated into two groups based on whether their treatment duration was up to six months or longer. The brace-related levels of stress and quality of life were investigated in both groups by using the Bad Sobernheim Stress Questionnaire and the Italian Spine Youth Quality of Life, respectively. The questionnaire scores were categorized as low, mean, and high. Our statistical analysis considered the proportion of patients falling into the three categories and the difference in crude score rates between the two groups. Values were considered significant at p < 0.05. The proportion of patients with brace-related stress and impaired quality of life was significantly lower in the group treated longer compared to the group that had only received treatment for up to six months (chi-square test, p < 0.0001). Overall, mean ± SD BSSQ scored 8.72 ± 4.91 and 12.89 ± 4.65 in group 1 and group 2, respectively (Mann-Whitney U test, p = 0.008), while ISYQoL scored 19.94 ± 8.21 and 16.07 ± 6.12, respectively. We argue that the differences could depend on both the physical and psychological adaptation patients make to their brace and that more support should be provided to patients when they start to wear their brace.